263 Factors associated with delay in reperfusion therapy (primary angioplasty) of patients with ST elevation myocardial infarction: data from the Regional Acute Myocardial Infarction Registry of Brittany. (23rd September 2015) - Le Breton, H; Coudert, I; Courcoux, H; Druelles, P; Moquet, B; Pennec, P Y; Treuil, J; Hacot, J P; Fillipi, E; Boulanger, B; Rialan, A; Rouault, G; et al.
Abstract : Background and Objectives: ORBI (French acronym for the Regional Acute Myocardial Infarction Registry of Brittany) was established in July 2006. Its main goal is to evaluate the time frame of reperfusion in the acute phase of ST segment myocardial infarction (STEMI) and determine factors associated with overlong delays. Programme: The ORBI registry was established in eight of the nine Interventional Cardiology Centres (ICC) in Brittany. All patients admitted to an ICC within 24 h of onset of symptoms with a final diagnosis of STEMI were included. Data were prospectively collected and entered into a computer database. Two groups of patients were distinguished: Group 1, those admitted directly to an ICC; Group 2, those who were taken to a general hospital before arriving at the ICC. Factors associated with a delay longer than that recommended were examined. Results: 2600 patients were included in the registry between 01 July 2006 and 15 April 2009. Of these, 89 patients had an MI when in hospital. Among the remaining 2511 patients, 1985 patients (76%) were in Group 1 and 526 (20%) in Group 2. Initial management was primary angioplasty in 1787 patients (69%), thrombolysis in 480 patients (18%) and medical treatment in 333 patients (13%). Time intervals for the 'angioplasty' subgroup are shown in figure 1 . The median interval between the first medical contact (as defined by the European Society of Cardiology) and balloon inflation was 96 min. In 70% of patients, this interval was longer than the recommended time of 120 min. Factors associated with delays were patient age (median time of 113―min in the over 75's vs 93―min in the under 75―years), initial management in a general hospital without a catheterisation laboratory (cath lab) (figure 2 ), no direct admission to the cathlab, and admission out of working hours. Discussion and Conclusion: Our registry data have highlighted that delays before access to coronary reperfusion for STEMI treated by primary angioplasty are longer than recommended (i.e. >120 min.) in 70% of patients. Only those patients who benefited from 'optimal' management, that is whose first call was to the emergency medical services (EMS) and who were admitted directly to the cath lab, underwent coronary reperfusion within the recommended time. The factors that contributed to delays were calling the general practitioner rather than the EMS, the number of health professionals involved in prehospital management, transport to a general hospital and transfer delays, and no direct admission to the cath lab. In conclusion, in cases of chest pain, the EMS should be called in order to reduce delays in reperfusion therapy. The EMS can deliver prehospital care and provide direct access to the cath lab, or offer thrombolysis if patients are too far away from the cath lab. Local evaluation of professional practices should help improve delays. Objectif(s), Contexte: L'Observatoire Régional Breton sur l'Infarctus du Myocarde (ORBI) a été mis en place en Juillet 2006. L'objectif premier de cet observatoire a été d'évaluer les délais de prise en charge à la phase aigue et les facteurs associés à une prise en charge tardive au delà des délais recommandés. Méthode: L'observatoire ORBI a été mis en place dans 8 des 9 de centres de Cardiologie Interventionnelle Bretons. Tout patient hospitalisé pour un IDM ST+ (diagnostic final retenu) dans les 24 heures suivant le début de la douleur est inclus. Toutes les données sont collectées prospectivement et centralisées sur une base de données informatisée. Les patients ont été séparés en deux groupes en fonction de leur prise en charge initiale: les patients du groupe 1 admis directement dans un centre de cardiologie interventionnelle (CCI) et les patients du groupe 2 préalablement hospitalisés dans un centre hospitalier général sans plateau technique de cardiologie interventionnelle. Les facteurs prédictifs d'un délai de prise encharge supérieur au délai recommandé on été étudiés. Résultats: 2600 patients ont été inclus entre le 01/07/2006 et le 15/04/2009. 89 patients ont présenté un infarctus alors qu'ils étaient hospitalisés. Parmi les 2511 patients restants, 1985 (76%) sont dans le groupe 1 et 526 (20%) dans le groupe 2. Parmi les 2600 patients, 1787 (69%) sont reperfusés par angioplastie primaire (groupe ATC), 480 (18%) sont traités par fibrinolyse, et 333 (13%) sont traités médicalement. Les délais de prise en charge des patients du groupe ATC sont rapportés figure 1 . Le délai médian entre le premier contact médical tel que défini par les recommandations de la société européenne de cardiologie et l'angioplastie coronaire est de 96 minutes. 70% des patients ont un délai premier contact médical – angioplastie supérieur au délai recommandé de 120 minutes. Les facteurs associés à une prise en charge tardive sont l'âge du patient (délai médian de 113' chez les patients d'âge ≤ 75ans vs 93' chez les patients < 75 ans), la prise en charge initiale dans un centre hospitalier sans plateau technique de cardiologie interventionnelle (figure 2 ), la non admission directe en salle de cathétérisme (44% des patients), l'heure d'admission en dehors des heures ouvrables. Impact clinique: La mise en place de cet observatoire permet de constater que les délais de reperfusion de l'infarctus du myocarde ST + traités par angioplastie sont supérieurs aux délais recommandés (120') chez 70% des patients. Seuls les patients avec un circuit de prise en charge optimal associant un premier appel au centre 15 et une admission directe en salle de cathétérisme ont une reperfusion dans les délais recommandés. Plusieurs facteurs concourent à ce « retard de prise » en charge: Appel du médecin généraliste et non du centre 15, le nombre d'intervenants médicaux en pré hospitalier, le passage par un CHG et les temps de transfert, l'absence d'accès direct en salle de cathétérisme. Conclusion: le circuit « optimal » avec un appel direct au centre 15 en cas de douleur thoracique doit être privilégié pour réduire les temps de reperfusion. Ceci permet une prise en charge pré hospitalière par une équipe SMUR, l'accès direct dans un centre de cardiologie interventionnelle et dans une salle de cathétérisme, et la fibrinolyse pour les patients pris en charge à distance d'un centre de cardiologie interventionnelle. La mise en place de programmes locaux d'Evaluation des Pratiques Professionnelles doit pouvoir concourir à l'optimisation de ces délais.